Corporate tax avoidance, accounting conservatism, and audit quality: Insights from European capital markets - Assawer, Elaoud; Anis, Jarboui (International Journal of Innovative Research and Scientific Studies, 2026)
This study examines whether accounting conservatism constrains corporate tax avoidance and whether external audit quality amplifies this effect. Using a panel of 388 firms listed in the STOXX Europe 600 index between 2012 and 2022, we employ multivariate regression techniques with firm fixed effects and a range of robustness checks. The results show that conservative accounting practices are negatively associated with tax avoidance, consistent with the role of conservatism as a disciplinary mechanism that limits opportunistic tax behavior. Moreover, the findings indicate that high-quality audits, proxied by Big 4 auditors, strengthen the conservatism–tax avoidance relationship, highlighting the complementary monitoring role of external auditors. Robustness analyses using alternative proxies and estimation methods confirm the stability of these results. This research contributes to the literature by integrating conservatism, audit quality, and tax avoidance into a unified governance framework, and by providing large-sample evidence from a European setting.